How Modernism and Postmodernism Perspectives Can Inform Counseling Practices? - Farhana Sabri (Bulletin of Counseling and Psychotherapy, 2023)
Counseling practices are informed by traditional approaches – identifying the root of the client’s problems or causes and removing them, thus bringing relief to the client. In psychoanalysis, the causes may be located in the deep recesses of the mind (repression); for the Rogerian they may reside in the client’s discrepancy between ideal-self and real self; while the cognitive counselor will trace the root of the problem to defective thinking. Social constructionism challenges these approaches to counseling practices.